Status of Procurement Planning, Issues and Challenges, and Proposed Interventions: Basis for Effective Service Delivery at the Department of Agrarian Reform (DAR) in Masbate Province - Ybañez, Mark Julius (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the status of procurement planning practices, issues and challenges, and proposed interventions as a basis for effective service delivery at the Department of Agrarian Reform (DAR) in Masbate Province. Anchored on Thai’s Public Procurement Theory, Osborne and Gaebler’s Service Delivery Theory, Hood’s New Public Management Theory, and the Input-Process-Output framework, the study employed a descriptive-survey research design. Data were gathered from thirty DAR Masbate employees directly involved in procurement planning using a validated researcher-made questionnaire and were analyzed through frequency count, percentage, weighted mean, standard deviation, and Pearson correlation. Findings showed that most respondents were female, married, aged 31–40 years, had 8–12 years of service, and were commonly assigned as BAC members and PPMP point persons. DAR Masbate demonstrated strong compliance with government procurement policies and guidelines, strong alignment with organizational goals, and strong timeliness and efficiency in procurement processes, while coordination and communication among units were generally rated agree. Issues and challenges were encountered only to a low extent, although limited qualified suppliers, insufficient training, and inaccurate cost estimates remained key concerns. The relationship between procurement planning practices and encountered challenges was weak and not statistically significant. The study concluded that DAR Masbate has generally strong procurement planning practices, but further improvement is needed in coordination, training, supplier engagement, cost estimation, monitoring, and digital procurement systems. The study supports SDG 8, SDG 9, SDG 11, SDG 16, and SDG 17 by promoting efficient public service delivery, institutional accountability, innovation, community support, and stakeholder collaboration. Its sustainability impact lies in strengthening governance, improving institutional processes, and supporting timely services for agrarian reform beneficiaries and rural communities.
Keywords: Agrarian Reform; DAR Masbate; Digital Procurement; Governance Sustainability; Procurement Planning; Public Procurement; Service Delivery; Supplier Management